Impact of designed Quairokkum Hydropower Plant reconstruction on the Syr Darya River ichthyofauna - Afanasyev , S. A.; Roman , A. M.; Dolinskii , V.L.; Karimov , H.N.; Erhashboev , I. K. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2020)
The article presents data on actual state of the fish fauna in the middle section of the Syr Darya River (including Quairokkum Reservoir and not-regulated river section downstream the dam), with regard to their migration behavior and protection status. Based on this list report also considers the actual state of the fish survival at Quairokkum HPP and analyzes of the main species affected and main factors increasing their chance to survive. Three methods to increase fish survival are proposed: by replacement of the turbines by more fish-friendly ones, by construction of the fish pass and by activation of fish deterrent devices in case of large fish accumulations.